Thermal response of ground for different depths on vertical ground source heat pump system in Elazig, Turkey - Esen, H.; Inalli, M. (Elsevier Sci Ltd, 2009)
The purpose of this study is to evaluate a heat pump system performance using the ground as a source and a sink of heat. The vertical ground source heat pump (VGSHP) system has a three single U-tube ground heat exchangers (GHEs) made of polyethylene pipe with a 40 mm outside diameter. The GHEs were placed in a vertical borehole (VB) with depths of 30 m (VB1), 60 m (VB2) and 90 m (VB3) and 150 mm diameters. The experimental results were obtained in cooling and heating seasons of 2006-2007. The monthly mean values of coefficient of performance for VB1, VB2 and VB3 states are obtained to be 3.37/1.93, 3.85/2.37 and 4.33/3.03 respectively in cooling/heating modes. The coefficient of performance increases with increasing the borehole depths of VGSHP system. The energy efficiency and exergetic efficiencies of the system components are determined. Results obtained from experimental measurement concluded that the VGSHP systems can be used for Elazig., Turkey climatic conditions.
Keywords: Ground source heat pump; Vertical heat exchanger; Coefficient of performance; Heating; Cooling